THE ROLE OF KARANG TARUNA BINA BAKTI REMAJA IN THE DEVELOPMENT OF GOA TOURIST OBJECTS PARANGPANGDI VILLAGE SIDAMULIH PANGANDARAN DISTRICT - Ramdani, Woy (Yayasan Panca Bakti Wiyata Pangandaran, 2023)
Based on the results of observations regardingthe role of Karang Taruna Bina Bakti Remaja in the development of Goa Parangpang tourist attraction in Sidamulih Village, Sidamulih District, Pangandaran Regency is not optimal. This is becauseKarang Taruna has not played a role in implementing the development policy for the Parangpang Goa tourist attraction, Karang Taruna lacks a strategy in implementing the Parangpang Goa tourism object development policy. Based on the background, then the formulation of the problem is: 1)What is the role of Karang Taruna Bina Bakti Pemuda in the development of the Parangpang Cave tourist attraction? 2) What are the obstacles of Karang Taruna Bina Bakti Remaja to play a role in the development of the Parangpang Cave tourist attraction? 3) What are the efforts to overcome the obstacles made by Karang Taruna Bina Bakti Remaja to play a role in the development of the Parangpang Cave tourist attraction? The research method used is descriptive analysis method. Informants as many as 7 people consisting ofHead of Sidamulih Village, Representative of Sidamulih Village, Chairman of Karang Taruna, Members of Karang Taruna and community representatives. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through data processing from interviews and observations to draw conclusions so that they can answer problems in research.Based on the research results thatthe role of Karang Taruna Bina Bakti Remaja in the development of Goa Parangpang tourist attraction in Sidamulih Village, Sidamulih District, Pangandaran Regencyhas not been implemented optimallywith little attentionfive dimensions of rolesin the development of tourist objects according to Santosa (2013: 66), namely the role as a policy, the role as a strategy, the role as a communication tool, the role as a dispute resolution tool and the role as therapy. There are perceived obstacles such as:there are still some Karang Taruna members who don't have enoughinitiative and activeness so that it is difficult to know the wishes and expectations of the village community, apart from that some Karang Taruna members were not serious in implementing the Parangpang Goa tourism object development program, furthermore the lack of good communication from the village government as the person in charge of the Parangpang Goa tourism object development program made it difficult to coordinate. There have been efforts such asEmphasizes all members of Karang Taruna to be proactive in communicating with the village community so that they can accommodate and gather information aboutthe wishes and expectations of the village community, besides thatprovide direction to Karang Taruna members to be serious so that they can show their sincerity in implementing the Parangpang Goa tourism object development program, other things build good two-way communication so that it makes it easier to coordinate the planning of the Parangpang Goa tourism object development program with implementation in the field.